2021
DOI: 10.1152/ajpcell.00116.2021
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy agents reduce protein synthesis and ribosomal capacity in myotubes independent of oxidative stress

Abstract: Chemotherapeutic agents (CAs) are first-line antineoplastic treatments in a wide variety of cancers. These agents can induce oxidative stress and promote muscle loss. CAs trigger local and systemic oxidative stress by increasing mitochondrial reactive oxygen species (ROS) and thereby stimulate protein breakdown. However, whether CAs can directly impact muscle protein synthesis independent of ROS production is currently unknown. To address this problem, first, we identified the mechanism by which oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Skeletal muscle growth requires a net increase in protein synthesis that is governed by the translation efficiency (amount of protein synthesis per unit RNA) and translation capacity (the total ribosomal content) within muscle fibers. [69][70][71][72] Translation is initiated by binding of eukaryotic initiating factor eIF4E to the 5′ Cap of mRNA strand.…”
Section: Tak1 Regulates Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle growth requires a net increase in protein synthesis that is governed by the translation efficiency (amount of protein synthesis per unit RNA) and translation capacity (the total ribosomal content) within muscle fibers. [69][70][71][72] Translation is initiated by binding of eukaryotic initiating factor eIF4E to the 5′ Cap of mRNA strand.…”
Section: Tak1 Regulates Protein Synthesismentioning
confidence: 99%
“…Skeletal muscle growth requires a net increase in protein synthesis that is governed by the translation efficiency (amount of protein synthesis per unit RNA) and translation capacity (the total ribosomal content) within muscle fibers. [ 69–72 ] Translation is initiated by binding of eukaryotic initiating factor eIF4E to the 5′ Cap of mRNA strand. The interaction between eIF4E and mRNA leads to the recruitment of eIF4G, eIF4A, and eIF4B factors to form eIF4F, the translation preinitiation complex, which recruits the 40S subunit of the ribosome to the mRNA strand.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic agents, which are commonly used to treat cancer and blunt tumor progression, have also a detrimental effect on skeletal muscle mass ( Barreto et al, 2016 ; Damrauer et al, 2018 ). A recent study showed in C2C12 myotubes that exposure to chemotherapeutic agents reduced protein synthesis, rRNA content, and Pol I-mediated rDNA transcription at the initiation step, suggesting that chemotherapy-induced anabolic deficits may partly result from impaired ribosome production ( Guo et al, 2021 ).…”
Section: Conclusion Perspectives and Future Research Directionsmentioning
confidence: 99%